Gestión administrativa y desempeño laboral de los colaboradores de la Municipalidad Distrital de San Pablo 2023 - Rengifo Gonzales, Jose Luis Hubert (2024)
The objective of this work is to establish the relationship between administrative management and work performance of the employees of the District Municipality of San Pablo 2022. It was a non-experimental research design, with a quantitative, cross-sectional, and descriptive level approach. The population was considered to be 90 employees of the District Municipality of San Pablo 2022, to whom a questionnaire was applied through the survey technique. Concluding that there is a high positive relationship between administrative management and work performance of the employees of the District Municipality of San Pablo 2022.